PTH-160 'One Stop' Jaundice Pathway in a District General Hospital: Evaluation of a pilot Pathway. (17th August 2016) - On, W; Mirza, N; Lewis, A; Tang, A; Koss, K; Saravanan, R
Abstract : Introduction: Jaundice warrants urgent investigations to exclude significant underlying disease. The British Society of Gastroenterology (BSG) commissioned a report in 2013 highlighting the importance of having a streamlined pathway for investigation of jaundice. 1 Macclesfield District General Hospital (MDGH) has a catchment area of approximately 0.2 million and established a jaundice pathway in 2013. The pathway serves as a 'ONE STOP INVESTIGATION' for jaundiced patients who have been referred from general practice (GP) or other specialties. Initial ultrasound triage by a Consultant Radiologist with hepatopancreatobiliary interest is followed by same day cross sectional imaging as appropriate. Our aim is to evaluate the performance/outcome of this pilot pathway. Methods: A retrospective review of all patients on the jaundice pathway was undertaken between March 2013 to October 2015.Data was collated and analysed from hospital electronic records and radiology database. Results: Thirty six patients were identified (19 males, 17 females)on the dedicated jaundice pathway . The median age of the patients was 73.5 years (range 36–92). 86% of patients (31/36) were investigated as outpatients. The median bilirubin level of the investigated patients was 122 µmol/L (range 29–497). The aetiologies of jaundice in this cohort of patients were: malignancies (n = 12), gallstone disease (n = 11), liver cirrhosis (n = 4), parenchymal liver disease (n = 6) and miscellaneous causes (n = 5). The median time from referral to investigations was 4 days (range 0–14) and the median time from investigations to an outcome was 2 days (range 0–20). Outcome was defined by a definitive management plan made after a review by a consultant and/or discussion in a MDT meeting. Overall, the median number of days from a patient being referred to obtaining an outcome was 8 days (range 0–28). For patients with malignancies (n = 12), the median time from referral to outcome was 9.5 days (range 6–28). This exceeds the expectations for the 2 week referral (2 WW) rule for patients with suspected malignancies. The patients with malignancies proceeded to undergo: endoscopic retrograde cholangiopancreatography (n = 5), percutaneous transhepatic cholangiography (n = 3), surgery (n = 2) and palliative treatment (n = 2). Conclusion: The jaundice pathway at MDGH has proven to be an effective pathway for patients to undergo investigations for jaundice. Majority of patients with jaundice can be managed as outpatients. Adequate resource management is needed to facilitate this dedicated pathway. This has now been adopted as a Gold Standard by the Central Manchester cancer network. Reference: 1 http://www.bsg.org.uk/images/Commissioning_report/BSG_Acute_Jaundice.pdf Disclosure of Interest: None Declared